Effects of water matrix on the rejection of neutral pharmaceutically active compound by thin-film composite nanofiltration and reverse osmosis membranes. (September 2022) - Shah, Izaz Ali; Ali, Sharafat; Yang, Zhe; Ihsanullah, Ihsanullah; Huang, Haiou
Abstract: Thin-film composite (TFC) nanofiltration (NF) and reverse osmosis (RO) membranes have been widely used to remove pharmaceutically active compounds (PhACs) from water and wastewater. However, limited information is available to present the rejection of neutral PhACs under complex water matrices. In this study, we used acetaminophen (AAP) as a representative neutral pollutant to study the effects of feedwater matrices on the rejection of neutral PhACs by NF and RO membranes. The results showed that the permeation of solutes and water through NF and RO membranes followed the classical solution-diffusion model. The corresponding permeability coefficients of AAP for the RO membrane showed good consistency, with average values ranging between (6.19–7.56) × 10 −6 μm s −1 in fresh and brackish feedwater. Meanwhile, the NF membrane exhibited stable AAP and NaCl fluxes as the applied pressure increased from 4.8 to 7.6 bar, suggesting an insignificant influence of convection on solute transport. In addition, a 10-fold increase in NaCl concentration reduced the average AAP permeability coefficient of the NF membrane by 57% (i.e. from 2.8 × 10 −5 m s −1 to 1.2 × 10 −5 m s −1 ), highlighting the relevance of co-existing ions to AAP transport. Furthermore, organic fouling resulted in enhanced AAP rejection by both NF and RO membranes at neutral pH level and medium applied pressure (i.e. 5.8 bar). Overall, this study provided important insights into the separation mechanism of TFC membranes for neutral PhACs, as well as the complex effects of the water matrix on the solute permeation processes. Graphical abstract: Image 1 Highlights: Effects of water matrix on the rejection of neutral pharmaceuticals were studied. Acetaminophen (AAP) rejection by NF and RO was pH-dependent. Organic fouling significantly increased AAP rejection with only a minor flux decline. Co-existing NaCl ions significantly impacted AAP permeation through the NF membrane. Solution-diffusion was the dominant rejection mechanism for the TFC membranes.